Problems of the organization electrical power market of the Central Asia - E. T. Alisherov (Путеводитель предпринимателя)
The article describes condition of electricity market and basics of pricingfor electricity in the electricity markets ofthe Commonwealth independent states. The actual problems of managing the power market.